Behaviors of Shelter Dogs During Harnessing and Leash Walks: Prevalence, Demographics, and Length of Stay - Betty McGuire; Bailey Guy; Miles Garland; Alexandra Jackson (Animals)
Length of stay is an important metric for animal shelters, and studies have identified physical characteristics of dogs, and some behaviors, that predict length of stay. Although many shelters include leash walks when introducing dogs to potential adopters, it is unknown whether behaviors during harnessing and walking influence length of stay. During 707 walks of 120 dogs at a New York shelter, we recorded excitable behaviors, such as jumping on handlers, grabbing the leash, and pulling on the leash, whose measures of prevalence were largely unknown for shelter dogs. We also examined whether dog demographic characteristics predicted behaviors and whether behaviors predicted length of stay. During harnessing, jumping on handlers had the highest prevalence (45%), while during walking, pulling on the leash was most prevalent (86%). Dog age was the most common demographic predictor of behaviors, with jumping on handlers and total pulls/walk decreasing with age. Grabbing the leash predicted length of stay, with longer stays for dogs that displayed this behavior. These two findings suggest that it would be beneficial for shelter staff and volunteers to focus training efforts on younger dogs and those that grab the leash.